2023
DOI: 10.1182/blood.2023020714
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of ENT3 drives histiocytosis and inflammation through TLR-MAPK signaling

Ruth Shiloh,
Ruth Lubin,
Odeya David
et al.

Abstract: Histiocytoses are inflammatory myeloid neoplasms often driven by somatic activating mutations in mitogen-activated protein kinase (MAPK) cascade genes. H syndrome is an inflammatory genetic disorder caused by germline loss-of-function mutations in SLC29A3, encoding the lysosomal equilibrative nucleoside transporter 3 (ENT3). Patients with H syndrome are predisposed to develop histiocytosis, yet the mechanism is unclear. Here, through phenotypic, molecular and functional analysis of primary cells from a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Moreover, the deletion of SLC29A3 in preclinical studies is associated with impaired autophagic regulation and altered proliferative potential in stem cells, which may account for some of the syndromic features described in H syndrome [ 12 ]. In addition, according to recent research, the defective function of ENT3, leading to accumulation of adenosine in lysosomes, could lead to abnormal stimulation of TLR7 and TLR8, resulting in MAPK signaling and activation of an inflammatory response driven by IFNs [ 9 , 10 , 18 ]. Of note, HCQ is a weak base that accumulates in the lysosomes of immune cells, where it exerts its action by interacting with membrane stability, inhibiting the proteolytic processing of TLR7 and thereby its activation [ 19 – 21 ].In this, HCQ may target quite directly the underlying molecular pathway involved in inflammation in H syndrome, providing hope for individuals suffering from this rare disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the deletion of SLC29A3 in preclinical studies is associated with impaired autophagic regulation and altered proliferative potential in stem cells, which may account for some of the syndromic features described in H syndrome [ 12 ]. In addition, according to recent research, the defective function of ENT3, leading to accumulation of adenosine in lysosomes, could lead to abnormal stimulation of TLR7 and TLR8, resulting in MAPK signaling and activation of an inflammatory response driven by IFNs [ 9 , 10 , 18 ]. Of note, HCQ is a weak base that accumulates in the lysosomes of immune cells, where it exerts its action by interacting with membrane stability, inhibiting the proteolytic processing of TLR7 and thereby its activation [ 19 – 21 ].In this, HCQ may target quite directly the underlying molecular pathway involved in inflammation in H syndrome, providing hope for individuals suffering from this rare disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that an alternative strategy may rely in targeting MAPK with MEK inhibitor therapy, which led to resolution of histiocytosis and inflammation in a patient with H syndrome [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study confirmed that the upregulation of SLC29A3 promotes the proliferation, invasion, and migration of pancreatic cancer cells and is associated with poor prognosis[ 41 ]. Another study revealed that SLC29A3 affects cytokine secretion and the inflammatory response by regulating the TLR-MAPK signaling pathway[ 42 ]. These studies provide important experimental and clinical evidence, thus confirming the critical role of PPIA and SLC29A3 in immune regulation and offering insights for a deeper understanding of the underlying mechanisms by which PPIA and SLC29A3 function in HCC.…”
Section: Discussionmentioning
confidence: 99%